2013
DOI: 10.1002/emmm.201202100
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 13 modulates intestinal epithelial barrier integrity in inflammatory diseases by activating TNF

Abstract: Several pathological processes, such as sepsis and inflammatory bowel disease (IBD), are associated with impairment of intestinal epithelial barrier. Here, we investigated the role of matrix metalloproteinase MMP13 in these diseases. We observed that MMP13−/− mice display a strong protection in LPS- and caecal ligation and puncture-induced sepsis. We could attribute this protection to reduced LPS-induced goblet cell depletion, endoplasmic reticulum stress, permeability and tight junction destabilization in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 82 publications
7
74
0
Order By: Relevance
“…[45][46][47] In agreement with this and with previous results from our group, 48,49 we detected LPS-induced intestinal leakage of orally administered dextran and increased bacterial translocation to the MLNs. In addition, both EGF injection (which assures an optimal gut barrier function) and treatment with antibiotics (which removes all intestinal flora) resulted in protection against LPS-induced lethality and this was correlated with reduced intestinal permeability.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…[45][46][47] In agreement with this and with previous results from our group, 48,49 we detected LPS-induced intestinal leakage of orally administered dextran and increased bacterial translocation to the MLNs. In addition, both EGF injection (which assures an optimal gut barrier function) and treatment with antibiotics (which removes all intestinal flora) resulted in protection against LPS-induced lethality and this was correlated with reduced intestinal permeability.…”
Section: Resultssupporting
confidence: 95%
“…This is lethal both in patients and in mouse models of sepsis and SIRS. [3][4][5][6][7][8] The Paneth cells, present in the crypts of Lieberkühn of the small intestine, contribute to mucosal immunity by sensing bacteria and releasing anti-microbial peptides, such as a-defensins, which are also known as cryptdins (crypt defensins) and other proteins such as lysozyme C and phospholipase A2. 9 These molecules are active against a broad spectrum of pathogens, such as bacteria and fungi, and they enable the Paneth cells to create a microenvironment protected from infection and overgrowth of luminal bacteria, which assures continuous stem cell replication to maintain mucosal integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The closest Mmp gene to Casp11 is Mmp13 (<1 cM). We found that the Mmp13 null mice (backcrossed R10 generations to C57Bl/6) originating from Stephen M. Krane’s lab and subsequently bred in our lab (C.L., Mmp13 Cli−/− mice) (Vandenbroucke et al, 2013) contain the Casp11 mutation despite intensive backcrossing to C57BL/6 (Figures 2A and 2B). Moreover, the Mmp13 Cli−/− mice were protected against death (Figure 2C) and hypothermia (Figure 2D) caused by S. enterica -derived LPS.…”
Section: Resultsmentioning
confidence: 93%
“…Considering that Mmp7 -, Mmp8 -, and Mmp13 null mice are protected against LPS lethality (Vandenbroucke et al, 2013; Vandenbroucke et al, 2012; Vandenbroucke et al, 2014), we analyzed the contribution of the Casp11 inactivating passenger mutation in this phenotype. The closest Mmp gene to Casp11 is Mmp13 (<1 cM).…”
Section: Resultsmentioning
confidence: 99%
“…Many 129 strains have a frameshift mutation in the Casp11 gene, making them functional nulls for Casp11 and therefore resistant to LPS challenge (6). Mice lacking Mmp13 have been reported to be resistant to LPS challenge (11), but this gene is less than 1 cM from Casp11 . The authors showed that B6.129-congenic mice that are 129-like for Casp11 and null for Mmp13 (a widely used congenic transgenic), are resistant to LPS, but when this congenic is backcrossed even further to B6 and they are rendered B6-like for Casp11 the Mmp13 null mice are susceptible to LPS challenge.…”
mentioning
confidence: 99%